Chapter 27: Cucurbit Production in Florida - Stephen M. Olson; Eric H. Simonne; William M. Stall; Pamela D. Robers; Susan E. Webb; Timothy G. Taylor; Scott A. Smith (EDIS, 2019)
This document is HS725, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.